Warm Circumpolar Deep Water at the Western Getz Ice Shelf Front, Antarctica - Assmann, Karen; Darelius, Elin Maria K; Wåhlin, Anna K; Kim, Tae Wan; Lee, Sang Hoon (Geophysical Research Letters, 2019)
The Getz Ice Shelf is one of the largest sources of fresh water from ice shelf basal melt in Antarctica. We present new observations from three moorings west of Siple Island 2016–2018. All moorings show a persistent flow of modified Circumpolar Deep Water toward the western Getz Ice Shelf. Unmodified Circumpolar Deep Water with temperatures up to 1.5 °C reaches the ice shelf front in frequent episodes. These represent the warmest water observed at any ice shelf front in the Amundsen Sea. Mean currents within the warm bottom layer of 18–20 cm/s imply an advection time scale of 7 days from shelf break to ice shelf front. Zonal wind stress at the shelf break affects heat content at the ice shelf front on weekly to monthly time scales. Our 2-year mooring records also evince that upwelling over the shelf break controls thermocline depth on subannual to annual time scales.
Keywords: Antarktis; geofysikk; glasiologi; isbrem; isshelf; observasjoner

Assessment of Atmospheric Reanalyses With Independent Observations in the Weddell Sea, the Antarctic - Jonassen, Marius O; Välisuo, Ilona; Vihma, Timo; Uotila, Petteri; Makshtas, Alexander P; Launiainen, Jouko (Journal of Geophysical Research: Atmospheres, 2019)
Surface layer and upper-air in situ observations from two research vessel cruises and an ice station in the Weddell Sea from 1992 and 1996 are used to validate four current atmospheric reanalysis products: ERA-Interim, CFSR, JRA-55, and MERRA-2. Three of the observation data sets were not available for assimilation, providing a rare opportunity to validate the reanalyses in the otherwise datasparse region of the Antarctic against independent data. All four reanalyses produce 2 m temperatures warmer than the observations, and the biases vary from +2.0 K in CFSR to +2.8 K in MERRA-2. All four reanalyses are generally too warm also higher up in the atmospheric boundary layer (ABL), with biases up to +1.4 K (ERA-Interim). Cloud fractions are relatively poorly reproduced by the reanalyses, MERRA-2 and JRA-55 having the strongest positive and negative biases of about +30 % and −17 %, respectively. Skill scores of the error statistics reveal that ERA-Interim compares generally the most favorably against both the surface layer and the upper-air observations. CFSR compares the second best and JRA-55 and MERRA-2 have the least favorable scores. The ABL warm bias is consistent with previous evaluation studies in high latitudes, where more recent observations have been applied. As the amount of observations has varied depending on the decade, season, and region, the consistency of the warm bias suggests a need to improve the modeling systems, including data assimilation as well as ABL and surface parameterizations.
Keywords: Sørishavet; Weddellhavet; atmosfæren; geofysikk; meteorologi; observasjoner

Quantarctica 3 released - Matsuoka, Kenichi; Skoglund, Anders; Roth, George; Melvær, Yngve; Tronstad, Stein (Fram forum, 2019)
Keywords: Antarktis; geofysikk; geografi; glasiologi; innlandsis; kartografi; satellite bilder

A note on digital elevation model smoothing and driving stresses - McCormack, Felicity S; Roberts, Jason L; Jong, Lenneke M; Young, Duncan A; Beem, Lucas H (Polar Research, 2019)
Ice-flow fields, including the driving stress, provide important information on the current state and evolution of Antarctic and Greenland ice-sheet dynamics. However, computation of flow fields from continent-scale DEMs requires the use of smoothing functions and scales, the choice of which can be ad hoc. This study evaluates smoothing functions and scales for robust calculations of driving stress from Antarctic DEMs. Our approach compares a variety of filters and scales for their capacity to minimize the residual between predicted and observed flow direction fields. We find that a spatially varying triangular filter with a width of 8–10 ice thicknesses provides the closest match between the observed and predicted flow direction fields. We use the predicted flow direction fields to highlight artefacts in observed Antarctic velocities, demonstrating that comparison of multiple observational data sets has utility for quality control of continent-scale data sets.
Keywords: Antarktis; geofysikk; glasiologi; innlandsis; isbreer; istykkelse

Influence of Summer Sublimation on δD, δ18O, and δ17O in Precipitation, East Antarctica, and Implications for Climate Reconstruction From Ice Cores - Pang, Hongxi; Hou, Shugui; Landais, Amaelle; Masson-Delmotte, Valérie; Jouzel, Jean; Steen-Larsen, Hans Christian; Risi, Camille; Zhang, Wangbin; Wu, Shuangye; Li, Yuansheng; An, Chunlei; Wang, Yetang; et al. (Journal of Geophysical Research: Atmospheres, 2019)
In central Antarctica, where accumulation rates are very low, summer sublimation of surface snow is a key element of the surface mass balance, but its fingerprint in isotopic composition of water (δD, δ18O, and δ17O) remains unclear. In this study, we examined the influence of summer sublimation on δD, δ18O, and δ17O in precipitation using data sets of isotopic composition of precipitation at various sites on the inland East Antarctica. We found unexpectedly low δ18O values in the summer precipitation, decoupled from surface air temperatures. This feature can be explained by the combined effects of weak or nonexistent temperature inversion and moisture recycling associated with sublimation-condensation processes in summer. Isotopic fractionation during the moisture-recycling process also explains the observed high values of d-excess and 17O-excess in summer precipitation. Our results suggest that the local cycle of sublimation-condensation in summer is an important process for the isotopic composition of surface snow, water vapor, and consequently precipitation on inland East Antarctica.
Keywords: Antarktis; geofysikk; iskjerner; paleoklimatologi; stabile isotoper

Subglacial Geology and Geomorphology of the Pensacola-Pole Basin, East Antarctica - Paxman, Guy J G; Jamieson, Stewart S R; Ferraccioli, Fausto; Jordan, Tom A; Bentley, Michael J; Ross, Neil; Forsberg, René; Matsuoka, Kenichi; Steinhage, Daniel; Eagles, Graeme; Casal, Tania G (Geochemistry, Geophysics, Geosystems, 2019)
The East Antarctic Ice Sheet (EAIS) is underlain by a series of low-lying subglacial sedimentary basins. The extent, geology, and basal topography of these sedimentary basins are important boundary conditions governing the dynamics of the overlying ice sheet. This is particularly pertinent for basins close to the grounding line wherein the EAIS is grounded below sea level and therefore potentially vulnerable to rapid retreat. Here we analyze newly acquired airborne geophysical data over the Pensacola-Pole Basin (PPB), a previously unexplored sector of the EAIS. Using a combination of gravity and magnetic and ice-penetrating radar data, we present the first detailed subglacial sedimentary basin model for the PPB. Radar data reveal that the PPB is defined by a topographic depression situated ~500 m below sea level. Gravity and magnetic depth-to-source modeling indicate that the southern part of the basin is underlain by a sedimentary succession 2–3 km thick. This is interpreted as an equivalent of the Beacon Supergroup and associated Ferrar dolerites that are exposed along the margin of East Antarctica. However, we find that similar rocks appear to be largely absent from the northern part of the basin, close to the present-day grounding line. In addition, the eastern margin of the basin is characterized by a major geological boundary and a system of overdeepened subglacial troughs. We suggest that these characteristics of the basin may reflect the behavior of past ice sheets and/or exert an influence on the present-day dynamics of the overlying EAIS.
Keywords: Antarktis; Sydpolen; Sørpolen; geofysikk; geomorfologi; glasiologi; innlandsis; subglasial geologi; subglasial topografi